One-step Synthesis of Deep Eutectic Solvents and Dissolution of Kraft Lignin - Merino Pz, Omar; Ceramacho, Ricardo; Martz-Palou, Rafael (Current Microwave Chemistry, 2023)
Lignin is a very abundant biopolymer with great potential to produce other high-value polymers with aromatic groups. Its valorization has been limited principally by its poor solubility in conventional organic solvents, which makes it difficult to deconstruct or transform it into other products with higher added value. In this work, we describe a one-pot procedure to prepare various Deep Eutectic Solvents and study their ability to dissolve Kraft lignin with the aid of microwave dielectric heating efficiently.Background: Lignin is a widely available aromatic biopolymer that is largely discarded or used as a low-value fuel when separated in paper production processes, so researchers are engaged in the development of lignin dissolution processes that allow its easy deconstruction and transformation into other products with higher added value.Objective: The main objective of this work is to find deep eutectic solvents capable of dissolving significant quantities of lignin with the aid of microwaves as a heating source.Method: The present work developed a simple, fast, and efficient method to dissolve lignin using Deep Eutectic Solvent/acetonitrile as solvents and irradiation by dielectric microwave heating.Results: Most of the DESs studied achieved significant dissolution of purchased lignin with common organic solvents by employing microwave irradiation as the heating method.Conclusion: Some DESs studied in this work are good alternatives as solvents for lignin solvent option of simple preparation from renewable precursors from biomass, such as glycerol, choline chloride, and urea, of low toxicity and cost for this application. The effectiveness of these systems appears to be based on molecular recognition by hydrogen bonding interactions involving the three species that make up the eutectic and the hydroxyl groups of the lignin. These solvents can be recovered and recycled.
Keywords: lignin